Effect of Maternal Obesity on Foetal Growth and Metabolic Health of the Offspring - Claudio Maffeis; Anita Morandi (Obesity Facts, 2017)
Maternal and placental conditions that are unfavourable for the embryo/foetus have long-lasting effects on different tissues and functions of the body, which may persist for life and, potentially, also be transmitted to the offspring. This review resumes current evidence on principle maternal and gestational conditions associated with unfavourable metabolic programming of the offspring, along with their mechanisms of action, either supposed or already proved.